Slowbalisation in the Context of US-China Decoupling - Alicia Garcia-Herrero (Intereconomics)
Abstract While it is too early to confirm the depth and the sustainability of this new trend towards slower globalisation, it may be happening in more domains than we are fully aware of, at least for the near term given the renewed backdrop of the Russia-Ukraine war and the wider use of sanctions globally.